Automation planning in an academic library (2012)
The application of computers to library house keeping operations and services has brought tremedous changes into the life cycle of information. These changes are obvious in the process of information generation, processing, storing, evaluation of use, dissemination, and disposition. Library automation is the modern methods that helps libraries and their users in effective use of library resources. In addition to improvement of services and operations efficiently and effectively, libraries are able to develop effective computer networks, towards optimum utilization of resources and facilities. The benefits of converting routine task and repetitive processes into some form of automation have been recognised and such use of automation became a long-term objective of library management. However, many academic libraries are still battling to find their feet in the application of computers to the operations in the library.This paper therefore highlighted some of the steps involved in planning for automation in academic libraries. These will guide those that are yet to automate their libraries in particular and those finding it difficult to have a breakthrough in general to accomplish the mission of automating their libraries. The study established that while the automation of an academic library is indispensable, there is a need for proper planning of library automation in order to harness the benefits of automation.Recommendations on how to have streamline library automation were made.